2021
DOI: 10.1186/s12939-021-01481-8
|View full text |Cite
|
Sign up to set email alerts
|

Affordability of current, and healthy, more equitable, sustainable diets by area of socioeconomic disadvantage and remoteness in Queensland: insights into food choice

Abstract: Background Poor diet is the leading preventable risk factor contributing to the burden of disease globally and in Australia, and is inequitably distributed. As the price of healthy foods is a perceived barrier to improved diets, evidence on the cost and affordability of current (unhealthy) and recommended (healthy, more equitable and sustainable) diets is required to support policy action. Methods This study applied the Healthy Diets ASAP (Australi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 56 publications
9
49
0
Order By: Relevance
“…The influence of such factors might explain why households in Greater Brisbane continue to purchase the current diet despite the recommended diet being 19% less expensive. This corresponds to findings of prior research using the Healthy Diets ASAP protocol in Australia that has shown that, under current policy settings, which include the exemption of "basic, healthy foods" from the Goods and Services Tax (GST) [9,10], the current diet is from 14% to 23% more expensive than the recommended diet in Brisbane [11,12], Canberra and Sydney [10], regional Victoria [13], Aboriginal communities in remote Australia [8] and in two large supermarket chains nationally [14].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The influence of such factors might explain why households in Greater Brisbane continue to purchase the current diet despite the recommended diet being 19% less expensive. This corresponds to findings of prior research using the Healthy Diets ASAP protocol in Australia that has shown that, under current policy settings, which include the exemption of "basic, healthy foods" from the Goods and Services Tax (GST) [9,10], the current diet is from 14% to 23% more expensive than the recommended diet in Brisbane [11,12], Canberra and Sydney [10], regional Victoria [13], Aboriginal communities in remote Australia [8] and in two large supermarket chains nationally [14].…”
Section: Discussionsupporting
confidence: 78%
“…The protocol comprises five sections: standardised current (unhealthy) and recommended (healthy, equitable and more sustainable) diet pricing tools; store location and sampling; calculation of household incomes; food price data collection; and analysis and reporting [11]. The protocol has been described in detail elsewhere [11] and applied in multiple studies [8][9][10][11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Testing the low SEG protocol used prices from a major city location. Regional and/or remote areas are likely to experience higher food prices [51] and a relative lack of 'own brand' products and budget supermarkets [52]. Therefore, diet cost and affordability results in this study reflect a 'best case scenario' for low SEGs.…”
Section: Limitationsmentioning
confidence: 78%